2013
DOI: 10.1248/bpb.b12-00965
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Apoptosis Inhibitor of Macrophages in a Rat Hypertension Model with Nephrosclerosis: Possible Mechanisms of Action of Olmesartan and Azelnidipine

Abstract: Stroke-prone spontaneously hypertensive (SHRsp) rats develop severe hypertension resulting in renal injury. We investigated apoptosis inhibitor of macrophages (AIM) expression in nephrosclerotic rats and the involvement of AIM in olmesartan (OLM)-and azelnidipine (AZN)-induced decreases in the number of macrophages infiltrating the kidney. We randomly assigned 20-week-old male SHRsp rats to receive one of the following substances every day for 12 weeks: water (vehicle), hydralazine (HYD), OLM, or AZN. Renal da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…This is one of the main pathologies underlying chronic kidney disease, and it may lead to ischemic changes in the glomeruli and interstitium, consequently compromising renal function. In a rat model of nephrosclerosis, immunohistochemistry analysis showed CD5L strongly expressed in macrophages that infiltrated the diseased kidney [70]. Furthermore, treatment with drugs that inhibited kidney damage and lowered macrophage infiltration reduced CD5L expression in renal tissue, thus suggesting the that CD5L expression is critical for the progression of nephrosclerosis [70].…”
Section: Atherosclerosismentioning
confidence: 99%
“…This is one of the main pathologies underlying chronic kidney disease, and it may lead to ischemic changes in the glomeruli and interstitium, consequently compromising renal function. In a rat model of nephrosclerosis, immunohistochemistry analysis showed CD5L strongly expressed in macrophages that infiltrated the diseased kidney [70]. Furthermore, treatment with drugs that inhibited kidney damage and lowered macrophage infiltration reduced CD5L expression in renal tissue, thus suggesting the that CD5L expression is critical for the progression of nephrosclerosis [70].…”
Section: Atherosclerosismentioning
confidence: 99%
“…Morphological and functional symptoms of progressive renal injury induced in these rats were alleviated by the inhibition of AT1R [21,22,23]. Similarly, the treatment with OLM significantly attenuated the number of TUNEL-positive cells in the animal model of progressive glomerular injury [23] and in the kidneys of hypertensive rats [24]. Moreover, in both cited studies, OLM-reduced apoptosis was associated with lower degree of interstitial fibrosis or glomerular sclerosis, respectively.…”
Section: Discussionmentioning
confidence: 70%
“…It suggested that AIM may have aggravated renal damage. Tadashi Uramat et al (18) established severe hypertension and induced kidney damage by using a model of spontaneous hypertension tendency (SHRsp) mice. After the treatment of hypertension with related drugs, it was found that the number of macrophages infiltrating into the glomeruli and interstitium was significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been numerous studies on the role of AIM in renal disease. For example, Tadashi Uramat et al (18) found in the hypertensive prone mouse model that reducing the expression of AIM and oxLDL (oxidized low-density lipoprotein, which have the effect of upregulating the expression of AIM) can effectively reduce the fibrosis of renal tissue. Similarly, Megumi Oshima et al (19) found that the area of AIM and macrophage deposition in renal tissue was positively correlated with the severity of proteinuria and eGFR decrease in patients with CKD.…”
Section: Introductionmentioning
confidence: 99%